2021
DOI: 10.1111/mcn.13189
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and breastmilk substitute use and feeding motivations among mothers in Bandung City, Indonesia

Abstract: Suboptimal breastfeeding is common in Indonesia, with only half of infants 0-5 months of age exclusively breastfed and feeding of breastmilk substitutes (BMS) highly prevalent among infants and toddlers. Various factors influence these feeding practices, including social norms, limited health system support and BMS manufacturer marketing practices. This cross-sectional survey aimed to identify the prevalence of breastfeeding and BMS feeding among children aged 0-35 months, explore socio-demographic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
0
16
0
4
Order By: Relevance
“…Another important thing to note is the fact that many women also attend private clinics and pharmacies when their child is ill, where they too receive infant feeding information. It has been documented both in Mexico and other countries that the promotion of breastmilk substitutes is a common practice in such facilities (8,66,67). For example, in a study in the Mexican states of Puebla and Chihuahua, authors documented that, when attending public and private health facilities, in 48.4% and 40.7% of cases, respectively, mothers of children younger than 24 months were recommended to give them a breast milk substitute.…”
Section: Discussionmentioning
confidence: 99%
“…Another important thing to note is the fact that many women also attend private clinics and pharmacies when their child is ill, where they too receive infant feeding information. It has been documented both in Mexico and other countries that the promotion of breastmilk substitutes is a common practice in such facilities (8,66,67). For example, in a study in the Mexican states of Puebla and Chihuahua, authors documented that, when attending public and private health facilities, in 48.4% and 40.7% of cases, respectively, mothers of children younger than 24 months were recommended to give them a breast milk substitute.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the evidence from studies in Mexico and other low- and middle-income countries (LMIC). Working outside the home has been linked to the reduction in EBF [ 37 , 38 , 39 ] by introducing FM [ 21 , 40 , 41 , 42 ]. For example, in Bangladesh, most mothers with formal employment in ready-made garment factories introduced FM as early as two months, despite knowing that breast milk is the sole ideal food for infants [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study also revealed that there was almost universal exposure to the marketing of breast milk substitutes. The authors proposed that health and nutrition claims from FM vendors may influence caregivers and their feeding choices [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, aggressive marketing of breast‐milk substitutes (BMS) play an important role in reducing the optimal duration of breastfeeding (Neves et al, 2021). Pervasive marketing of BMS have been shown to adversely impact knowledge, intention, beliefs, self‐efficacy and social norms related to breastfeeding (Green et al, 2021). COVID‐19 pandemic has created an additional threat to optimal breastfeeding, as BMS companies have capitalized on the fear of possible transmission of the infection through breast milk, to promote the use of BMS products (Ching et al, 2021).…”
Section: Introductionmentioning
confidence: 99%